Pregled meritev vsebnosti suspendiranega materiala v Sloveniji in primer analize podatkov - Bezak, Nejc (Gradbeni vestnik, 2013)
Natural turbidity in rivers is an important hydrological parameter, which is directly correlated with soil erosion, ecological river conditions and also with extreme weather situations. The measurements of suspended material in Slovenian rivers beganin 1955 at the hydrological station Veliko Širje on the Savinja river. This paper summarizes turbidity measurements, which were carried out by the Slovenian Environment Agency. The detailed description of stations which have more than 3 years of continuous measurementsis given. The statistical analysis of daily turbidity data for the hydrological stationGornja Radgona on the Mura river was made. We analysed seasonal characteristics ofdischarges and concentrations of suspended sediments, then the frequency analysis wasmade, and finally the correlation coefficients between discharges, transport and concentrations of suspended material was calculated. These analyses are a basis for improvingthe understanding of properties of suspended sediments transport processes.
Keywords: fluvial sediments; hidrologija; hidrometrija; hydrology; hydrometry; kalnost; probability analysis; rečni sedimenti; Slovenia; Slovenija; turbidity; verjetnostne analize